Decrease in Cryptosporidium parvum Oocyst Infectivity In Vitro by Using the Membrane Filter Dissolution Method for Recovering Oocysts from Water Samples - Carreno, Ramon A. (American Society for Microbiology, 2001)
Exposure of Cryptosporidium parvum oocysts to solutions used for cellulose acetate membrane (CAM) dissolution filtration reduced their infectivity in HCT-8 cells. Ethanol (95% [vol/vol] and 70% [vol/vol]) alone and short exposure times to acetone decreased infectivity. These findings contrast with similar experiments using excystation assays and infectivity in mice.